Cinética da expressão de IL-6, CCL2 e CCL3 nos tecidos periodontais durante o movimento dentário ortodôntico - Davidson Frois Madureira (2012)
Introduction: Mechanical loading induces remodeling of periodontal ligament and alveolar bone, which is mediated by cytokines and chemokines. This study investigated the kinetics of IL-6, CCL2 and CCL3 levels in periodontal ligaments subjected to orthodontic forces. Methods: 64 human premolars were used in this split-mouth design study. The experimental group consisted of premolars subjected to a 0.980 N apical direction force for 3 hours, 15 hours, 3 days, 12 days or 21 days using a .017 x .025 TMA cantilever. The contralateral teeth, which did not contain orthodontic appliances, were used as controls. The premolars were extracted for orthodontic reasons and the periodontal ligaments were scraped for analysis of cytokine levels by ELISA. Results: Compared with the control group, an increase in CCL2 was observed on days 3 and 12, and increases in IL-6 and CCL3 were observed on day 12 in the experimental group. Conclusions: Our data demonstrated a differential expression of IL-6, CCL2 and CCL3 in human periodontal ligament after mechanical loading, which may reflect distinct roles of these molecules in the bone remodeling process.